2022
DOI: 10.3390/molecules27186011
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum, Vanadium, and Tungsten-Based Catalysts for Sustainable (ep)Oxidation

Abstract: This article gives an overview of the research activity of the LAC2 team at LCC developed at Castres in the field of sustainable chemistry with an emphasis on the collaboration with a research team from the University of Zagreb, Faculty of Science, Croatia. The work is situated within the context of sustainable chemistry for the development of catalytic processes. Those processes imply molecular complexes containing oxido-molybdenum, -vanadium, -tungsten or simple polyoxometalates (POMs) as catalysts for organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…85–88 This leads to the formation of a moiety of the type {Mo-OOR} responsible for the oxygen atom transfer step to the olefin, giving the epoxide product (plus the coproduct of TBHP, namely tert -butanol). These mechanistic considerations may also apply for W-catalysed olefin epoxidation, 89–92 and other metals ( e.g. , active oxidizing species possessing the moiety {M-OOR} were reported for Ta-containing catalysts in olefin epoxidation 93 ).…”
Section: Resultsmentioning
confidence: 98%
“…85–88 This leads to the formation of a moiety of the type {Mo-OOR} responsible for the oxygen atom transfer step to the olefin, giving the epoxide product (plus the coproduct of TBHP, namely tert -butanol). These mechanistic considerations may also apply for W-catalysed olefin epoxidation, 89–92 and other metals ( e.g. , active oxidizing species possessing the moiety {M-OOR} were reported for Ta-containing catalysts in olefin epoxidation 93 ).…”
Section: Resultsmentioning
confidence: 98%
“…Transition metal polyoxometalates are used as catalytically active materials in synthetic processes and are promising in the field of hydrogen energy. , The polyoxorhenate discovered is likely to find application in the field of organic catalysis in olefin metathesis reactions or other similar processes. The fact of the formation of complex rhenium polyoxometalates and the absence of such for technetium under the specified conditions can be used for a highly specialized process for separating rhenium and technetium from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrated HReO 4 solutions were tried in dozens of different options with very limited or no success. It was clear from ref 17 that the [Tc 20 O 68 ] 4− polyoxoanion was stabilized by reduction of Tc in the central tetramer of Tc 4 O 4 to the Tc(V) oxidation state while in the rest 16 Tc-oxometalate groups, technetium stood as Tc(VII). However, Re(VII) is a bit more stable compared to Tc(VII), and polyoxometalate of Re 20 O 68 analogous to Tc could not be obtained because the reduction of Re does not occur in these conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the trade-off in the sustainable shift of oxidant/catalyst pairs, complex ESAs' reactions are often accompanied by the use of transition-metal complexes as reaction catalysts. The most sought-out structures (in particular with industrial applications) are manganese-salen complexes [23], metalloporphyrins [24][25][26] and other transition metal complexes containing titanium, molybdenum or vanadium [27][28][29][30]. Indeed, solidphase industrial epoxidation catalytic processes are extensively reported in the literature Epoxidation Small Alkenes and Allylic Alcohols Some of the challenges of ESAs had already been addressed by industrialists, such as feedstock consumption and capital/energy expenditure, while reaction parameter developments were based on designing novel catalysts [8,9].…”
Section: Introductionmentioning
confidence: 99%